Tunneled Epidural Analgesia for Refractory Scrotal Cancer Pain: A Case-Based Evaluation of Therapeutic Efficacy - Nur Azza, Kamala Kan; Tomo, Wahyu Kartiko; Darwito, Darwito; Puspitasari, Ika; Mahmud, Mahmud; Widyastuti, Yunita (Academic Hospital Journal, 2025)
Background: Scrotal Squamous Cell Carcinoma (SCC) is a rare malignancy. Although SCC typically demonstrates slow progression, in advanced stages with significant size, it can cause considerable pain due to mass effect and local tissue invasion. The management of cancer-related pain encompasses a wide spectrum of approaches, ranging from pharmacologic to surgical interventions. In cases where patients become intolerant to the side effects of pharmacologic therapies and adequate pain relief cannot be achieved, while surgical options are either not feasible, interventional pain management may offer an effective alternative. Tunneled Epidural Analgesia represents one such interventional technique that can be considered for refractory pain. This case report aims to evaluate the efficacy of tunneled epidural analgesia administration in managing intractable pain associated with advanced scrotal SCC.Materials and methods: This case report is structured according to the CARE (Case Report) guideline. The study was conducted at UGM Academic Hospital, where the patient received evaluation and treatment.Case: A 65-year-old male diagnosed with SCC presented experiencing refractory cancer pain. Despite receiving conventional analgesic therapy, he experienced no significant pain relief and developed adverse effects. Pain management was subsequently escalated to an interventional approach using a bupivacaine 0.125% and fentanyl 25 mcg administered via a tunneled epidural drug delivery system. This intervention resulted in effective pain control, enabling him to do daily activities. With this modality, the pain remained well managed, although occasional breakthrough pain occurred, which was successfully managed with 1% lidocaine as a rescue analgesic.Conclusion: Tunneled epidural analgesia using a combination of opioid and bupivacaine has demonstrated effectiveness in the management of refractory scrotal cancer pain.